High-performance low-cost microalloyed steel for automobile I-shaped axle and preparation method of microalloyed steel
By adding Ti elements to 40Cr steel and optimizing the heat treatment process, the TiC precipitation phase is formed, which solves the problem of low mechanical performance after heat treatment of automotive axle materials, and realizes high-performance and low-cost microalloy steel preparation, which significantly improves the strength of the material and fatigue life.
Patent Information
- Application Number
- CN202411337726.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-25
- Publication Date
- 2025-01-10
AI Technical Summary
The existing automotive axle material 40Cr steel has low mechanical properties after heat treatment, resulting in premature fracture failure, and the addition of alloy elements such as vanadium and niobium is high cost and the strength improvement is limited, making it difficult to meet the needs of production and application.
Add Ti elements to 40Cr steel, control the N content below 50ppm, ensure that the C/Ti atomic ratio is between 20 and 30, and form a TiC precipitation phase. Through quenching + tempering heat treatment process, the austenite grains are pinned to suppress Grain boundaries move, improving material strength and toughness.
It significantly improves the yield strength, tensile strength and fatigue life of automotive I-shaped axle materials, reduces material costs, and realizes high-performance and low-cost microalloy steel preparation, extends service life and enhances safety.
Smart Images

Figure CN119287263A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to high-performance and low-cost micro-alloy steel for automobile I-shaped axles and a preparation method thereof, belonging to the technical field of materials. Background Art
[0002] The automobile axle is an important part of the automobile chassis. It plays the role of bearing weight and connecting leaf springs, tires, etc. It also forms a steering system with parts such as tie rods and steering knuckles, which has a great impact on the safety and operational stability of the entire vehicle. In recent years, as the country has aimed at achieving the carbon emission reduction and carbon peak target, it has introduced many policies in many aspects such as energy conservation and energy saving and consumption reduction, requiring automobile parts to be further reduced in weight, especially automobile axles, which are required to reduce weight by more than 20%. Automobile energy consumption mainly depends on the displacement of the engine and the total weight of the car. Research figures show that if the weight of the entire vehicle is reduced by 20%, the fuel efficiency can be improved by more than 16%. Therefore, using new materials and new processes to reduce the weight of the axle and achieve lightweight automobile axles is of great significance to the fuel economy of the entire vehicle.
[0003] 40Cr steel is a low-alloy high-strength structural steel. It has been widely used in various engineering structures because of its excellent comprehensive mechanical properties and good cutting performance. Especially in the automotive parts industry, 40Cr steel, as a key core material for automobile axles, plays a vital role in the safe operation of automobiles. Due to the low mechanical properties of automobile axles after heat treatment, premature fracture failure occurs during service, limiting the further development of the company. Therefore, it is very necessary to make targeted improvements to the current axle materials to further improve the comprehensive properties of 40Cr steel, especially the yield strength and tensile strength, thereby improving its fatigue performance, thereby extending its service life and enhancing safety, while reducing the weight of structural materials, improving the core competitiveness of products, and avoiding being eliminated by the market. Chinese patent (publication number: CN108220778A) a niobium-vanadium composite reinforced high-strength axle steel and its production method, the chemical composition and mass percentage of the axle steel are: C: 0.15-0.20%, Si: 0.20-0.40%, Mn: 1.40-1.60%, P≤0.015%, S≤0.010%, V≥0.04%, Nb≥0.04%, Ti≥0.01%, Als≤0.045%, the remainder is Fe and unavoidable impurity elements; add microalloying elements vanadium and niobium on the basis of carbon and manganese low alloy steel, through the vanadium and niobium microalloying elements in the steel to form stable carbides and nitrides with carbon, produce fine grain strengthening and precipitation strengthening, and cooperate with controlled rolling and controlled cooling to form pearlite + ferrite structure, obtain high strength, high toughness, hot forming bridge shell steel, tensile strength ≥ 670MPa, elongation ≥ 18%, yield strength ≥ 500MPa, low temperature -20℃ impact energy ≥ 47J. Its disadvantage is that it uses a variety of alloying elements such as vanadium and niobium, not only the cost is significantly higher, but also the improvement of strength is limited, the tensile strength can only reach 710MPa, the yield strength can only reach 540MPa, it is difficult to meet the needs of production applications.
[0004] Fujian Tiechima Lightweight Axle Co., Ltd. and the Institute of Metal Research, Chinese Academy of Sciences jointly developed new materials for automotive I-beam axles. The Institute of Metal Research, Chinese Academy of Sciences is responsible for material research and development, and the company is responsible for the industrialization of new materials. Based on the previous research work, the Institute of Metal Research, Chinese Academy of Sciences successfully developed a new type of high-performance automotive I-beam axle material through composition design and organizational regulation, and obtained the laboratory composition window of the new material. In collaboration with the company, a new type of Ti-containing microalloy steel for automotive I-beam axles was newly developed and put into use. After matching heat treatment, the comprehensive performance of the new material automotive I-beam axle has been further improved, especially the fatigue performance has been significantly improved. It is expected to be used in automotive I-beam axles to achieve lightweight automotive I-beam axles. Summary of the invention
[0005] The purpose of the present invention is to provide a high-performance, low-cost microalloy steel for automobile I-shaped axles and a preparation method thereof, by adding a certain amount of Ti element to 40Cr steel, and at the same time, controlling the N content in the invention material to be less than 50ppm, in order to avoid the formation of large particles of TiN inclusions, while ensuring that the atomic ratio of C / Ti is between 20 and 30. In this way, a part of the carbon can be dissolved into the matrix, and the other part is combined with all the Ti elements of the matrix to form a TiC precipitation phase, and TiC can effectively pin austenite grains and inhibit the movement of austenite grain boundaries, thereby obtaining finer grains, improving the strength and hardness of the material, and realizing casting instead of forging. By adopting a quenching and tempering heat treatment process, after solid solution water cooling at 810-850°C, TiC can effectively pin austenite grains and inhibit the movement of austenite grain boundaries, thereby obtaining finer grains and improving the mechanical properties of the material. In addition, by tempering at 500-550°C, tempered martensite structure and precipitation phases such as TiC dispersed and evenly distributed inside the grains can be obtained, further improving the strength and plasticity of the material, and ultimately obtaining an invented material with the best combination of strength and plasticity, ensuring the fatigue performance of the invented material.
[0006] The technical solution of the present invention is:
[0007] The invention discloses a high-performance and low-cost micro-alloy steel for automobile I-shaped axles, wherein the chemical composition thereof is, by weight percentage, 0.35-0.50% C, 0.50-0.60% Mn, 0.1-0.5% Si, 0.65-0.85% Cr, 0.01-0.10% Ti, 0.03-0.04% Mo, P<0.01%, S<0.01%, O<0.0040%, N<0.0050%, and the balance is iron.
[0008] The high-performance and low-cost microalloy steel for automobile I-shaped axles preferably contains 0.060-0.08% Ti and the atomic ratio of C to Ti is controlled between 20 and 30.
[0009] The high-performance and low-cost micro-alloy steel for automobile I-axles preferably has N<0.0020%.
[0010] The method for preparing high-performance and low-cost microalloyed steel for automobile I-shaped axles comprises the following steps:
[0011] (1) mixing the chemical components in proportion, and obtaining an automobile I-axle ingot through smelting and casting;
[0012] (2) The obtained automobile I-axle ingot is directly heat treated.
[0013] The method for preparing high-performance and low-cost microalloyed steel for automobile I-beam axles comprises the following steps: first, heat-treating the steel at 830°C±20°C for 30-60 minutes, followed by water quenching to room temperature; and then heat-treating the steel at 500-550°C for 90-120 minutes, followed by water cooling to room temperature.
[0014] The preparation method of the high-performance and low-cost micro-alloyed steel for automobile I-beam axles, the performance indicators of the high-performance and low-cost micro-alloyed steel for automobile I-beam axles after heat treatment are as follows: the yield strength reaches more than 1000MPa, the tensile strength reaches more than 1150MPa, the elongation reaches more than 10%, the cross-sectional shrinkage reaches more than 35%, and the fatigue life B50 reaches more than 550,000 times.
[0015] The design concept of the present invention is as follows:
[0016] 1) Addition and optimization of Ti content: First, when a certain amount of Ti is added to 40Cr steel, in order to avoid the formation of large particles with angular structure TiN harmful inclusions, such inclusions are prone to stress concentration, which leads to a significant reduction in the fatigue performance of the material. Therefore, the content of N in the material must be strictly controlled to ensure that the trace addition of Ti will not have a negative impact on the microstructure and mechanical properties of the steel, especially the fatigue performance of the material. Therefore, the nitrogen content in the steel of the present invention is controlled to be less than 50ppm. Secondly, in order to ensure the complete precipitation of Ti in the solid solution matrix in the matrix, by optimizing the C element content in the steel, ensuring that the C:Ti atomic ratio is between 20 and 30, and obtaining a refined grain structure by pinning the austenite grains with the TiC precipitation phase, thereby ensuring that the steel has excellent strength and toughness matching.
[0017] 2) Innovation of heat treatment system: In order to solve the problem of insufficient strength of the microstructure obtained after traditional quenching and tempering treatment. The material of the present invention innovatively adopts a quenching + tempering heat treatment system. First, quenching heat treatment is adopted to ensure that the microstructure of the invention material is a lath martensite structure. Lath martensite has higher strength and hardness than the structure of traditional quenching and tempering treatment due to its high carbon content and distorted lattice structure. The subsequent tempering treatment system aims to obtain tempered martensite structure and ensure the dispersed and uniform precipitation of TiC carbides, which not only improves the strength of the material, but also improves the plasticity and toughness of the invention material to a certain extent. The present invention adopts a quenching + tempering heat treatment process to obtain a typical martensitic structure, which can significantly improve the comprehensive performance of the microalloyed steel of the automotive I-beam front axle, especially greatly improve the fatigue performance of the material.
[0018] The content ranges of the main elements in the present invention are described as follows:
[0019] C: C forms Fe with Ti and Cr elements 3C and TiC carbides precipitate at interfaces such as original austenite grain boundaries and lath boundaries, which can pin dislocations and hinder the movement of interfaces, play a role in precipitation strengthening, and effectively improve the strength of the material. The increase in carbon content can improve the strength and hardness of the material, but too high a carbon content will reduce the plasticity and toughness of the material, and also reduce the welding performance of the material. Therefore, the carbon content in the steel of the present invention is optimized and controlled to be 0.35wt% to 0.50wt%.
[0020] Mn: Mn can enhance the strength and toughness of steel through solid solution strengthening mechanism. Mn replaces iron atoms in the steel lattice, produces distortion, and increases the yield and tensile strength of the material. At the same time, Mn is an austenite forming element, which can significantly reduce the martensite formation temperature of steel. S point, improving the hardenability of the material. However, the addition of manganese will affect the temperature at which TiC is completely dissolved into the matrix. Therefore, the manganese content in the steel of the present invention is optimized and controlled to be 0.50wt% to 0.60wt%.
[0021] Si: The Si element plays several key roles: First, as a deoxidizer, Si reacts with oxygen to form silicon dioxide (SiO 2 ), thereby reducing the oxygen in the molten steel, thus improving the purity and overall quality of the steel. Secondly, Si enhances the strength and hardness of the material through a solid solution strengthening mechanism, because Si atoms replace iron atoms in the steel lattice, introducing tiny distortions, making it more difficult for dislocations to move, thereby improving the mechanical properties of the steel. However, the silicon content needs to be carefully controlled, and too high a Si content may affect the welding performance of 40Cr steel. Therefore, the silicon content in the present invention is controlled to be: 0.10wt% to 0.50wt%.
[0022] Cr: Cr can reduce the concentration of carbon in pearlite and the limit concentration of carbon in austenite, slow down the decomposition rate of austenite, and improve the hardenability of steel. At the same time, it can form chromium carbide with carbon during tempering, significantly improving the strength of steel, while improving the wear resistance of steel, and easily obtaining a lower surface roughness. Therefore, the chromium content in the present invention is optimized and controlled to be 0.65wt% to 0.85wt%.
[0023] Ti: Ti element plays a role in refining grains in the 40Cr material system. TiC shows extremely high thermodynamic stability and is difficult to dissolve back into the matrix even at high temperatures. During the solid solution process at 810-850°C, TiC with larger particles is distributed near the grain boundaries. This preferential distribution effectively inhibits grain boundary migration, thereby maintaining the grain size of the invented material and significantly improving the strength and toughness of the material. However, when its content exceeds 0.1wt%, coarse TiC particles will be formed, reducing the mechanical properties of the material. Therefore, the Ti content in the present invention is controlled to be: 0.01wt%-0.10wt%, and further optimized to be controlled to be 0.06wt%-0.08wt%.
[0024] Mo: Molybdenum can promote solid solution strengthening and the formation of carbides. It replaces iron atoms in the steel lattice, produces distortion, thereby hindering the movement of dislocations, increasing the yield and tensile strength of the material, and dissolves in carbides to improve the stability of carbides. At the same time, during the tempering process, molybdenum promotes the formation of carbides between Cr and C, thereby improving the strength of the steel. Therefore, the molybdenum content in the present invention is optimized and controlled to be 0.03wt% to 0.04wt%.
[0025] S, P: In the production of steel, phosphorus and sulfur are regarded as harmful impurities because they can significantly reduce the overall performance of steel. The presence of phosphorus increases the cold brittleness of steel, reduces the cohesion of grain boundaries, thereby reducing the toughness and plasticity of the material, and also affects the welding performance, causing welded joints to be prone to cracks. On the other hand, sulfur will increase the hot brittleness tendency of steel, especially during high-temperature processing. At the same time, excessive sulfur will also affect the mechanical processing quality of steel and reduce the strength and toughness of the material. Therefore, the content of sulfur and phosphorus in the steel of the present invention is strictly controlled to: S <0.01wt%, P <0.01wt%.
[0026] O: Control of the O content in steel is also crucial. When the O content exceeds a certain limit, brittle oxide inclusions will form in the steel, significantly reducing its mechanical properties. Studies have shown that once the oxygen content in 40Cr steel exceeds 0.005wt%, its strength and plasticity will decrease. Since 40Cr steel often bears heavy loads in automotive I-beam axles, its sensitivity to stress concentration caused by oxide inclusions cannot be ignored. Therefore, the oxygen content in the steel of the present invention is strictly controlled: O<0.004wt%.
[0027] N: The presence of N element has a significant impact on its performance. Especially in steels containing titanium (Ti), N easily forms large particles of TiN (titanium nitride) with Ti. Due to the high thermodynamic stability of TiN, this inclusion is difficult to eliminate. In addition, due to the typical angular structure of TiN, stress concentration will form, causing cleavage fracture of the material, deteriorating the strength and plasticity of the material, especially fatigue performance. Therefore, in order to avoid the formation of TiN inclusions and their negative impact on material properties. Therefore, the N content in the steel of the present invention is controlled to N<0.0050wt%, and further optimized to N<0.0020wt%.
[0028] The advantages and beneficial effects of the present invention are:
[0029] 1. The present invention creatively adds a certain amount of Ti element to 40Cr material, controls the atomic ratio of C and Ti between 20 and 30, ensures that TiC is formed on the grain boundary after smelting and casting, and the TiC existing on the grain boundary plays a role in pinning the grain boundary and refining the grain during the heat treatment process, thereby improving the strength and toughness of the material and reducing the degree of material segregation to a certain extent. In addition, due to the low price of Ti element, on this basis, a high-performance and low-cost micro-alloy steel for automobile I-shaped front axles is developed.
[0030] 2. Optimization of heat treatment system: By changing the traditional quenching and tempering heat treatment scheme, the quenching + tempering rapid cooling method is adopted to ensure the presence of larger TiC (480-520nm) in the original austenite on the grain boundary during the quenching (solid solution) process, and smaller TiC (20-50nm) is formed inside the martensite laths and grains during the tempering process. The formation of dual-size TiC precipitation phase can ensure that the material has an excellent combination of strength and plasticity.
[0031] 3. The present invention adopts Ti microalloying to obtain a preparation process for a new high-performance and low-cost I-shaped front axle for light and heavy trucks. The comprehensive performance is greatly improved compared with commercial 40Cr steel, the yield strength is increased to 1000MPa compared with traditional 40Cr steel, the tensile strength is increased to 1150MPa, and especially the B50 fatigue life is increased to more than 550,000 times.
[0032] 4. The present invention provides an efficient and economical manufacturing method of high-performance and low-cost microalloy steel for automobile I-shaped front axles. Under the premise that the comprehensive performance of the material is guaranteed, the casting process can be used instead of the forging process to further save the mold and forging costs, thereby greatly reducing the material cost, and the enterprise can achieve energy saving and consumption reduction and cost reduction and efficiency improvement. In addition, the material of the present invention can better support the rapid development of my country's automobile industry, and at the same time, it also provides a new idea for the development and application of low-cost and high-performance materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1Schematic diagram of the metallographic structure of Example 1 after heat treatment.
[0034] Figure 2 This is a schematic diagram of the SEM structure of Example 1 after heat treatment.
[0035] Figure 3 Schematic diagram of the TEM structure of TiC after heat treatment in Example 2.
[0036] Figure 4 Schematic diagram of the metallographic structure of Comparative Example 1 after heat treatment.
[0037] Figure 5 This is a schematic diagram of the SEM structure of Comparative Example 1 after heat treatment.
[0038] Figure 6 Schematic diagram of the metallographic structure of inclusions in Comparative Example 2.
[0039] Figure 7 The SEM diagrams of the tensile fracture of Comparative Example 2 are shown in Figure 2. The magnification of (a) is 10×, and the magnification of (b) is 50×. DETAILED DESCRIPTION
[0040] In the specific implementation process, the innovation of the present invention is to add a certain amount of Ti element to 40Cr steel through optimization, optimize the C element content and the atomic ratio of C and Ti elements, strictly control the N element content, ensure that Ti can be completely dissolved into the matrix during the smelting process, and avoid the formation of large-particle TiN inclusions. The above-mentioned composition control strategy is helpful to promote the formation of titanium carbide (TiC) and dispersed precipitation on the original austenite grain boundary. These carbides can effectively pin the austenite grains to obtain a microstructure with uniform and fine grain size. The size range of austenite grains is 40μm to 60μm. In addition, the segregation degree of the material is reduced to a certain extent; heat treatment is directly carried out after casting, and the martensitic structure is obtained by quenching by changing the traditional heat treatment process. Through the subsequent tempering process, the carbide (TiC) can be uniformly dispersed and precipitated in the martensitic structure, thereby achieving the best combination of mechanical strength and toughness of the automobile I-shaped axle material. The automobile I-shaped front axle can adopt a casting-instead-forging process, thereby saving mold and forging costs and achieving low cost of the automobile I-shaped axle.
[0041] The following examples and drawings will further illustrate the present invention, but are not intended to limit the present invention. The steel in the examples and the materials in the comparative examples are processed into standard tensile specimens after smelting and heat treatment for mechanical property testing, and the fatigue performance is tested on a dedicated test bench for the fatigue performance of an automobile I-shaped front axle B50 (3.5 times the load).
[0042] The preparation process of the high-performance and low-cost microalloy steel for the automobile I-shaped front axle of the present invention is: batching → smelting → casting → heat treatment. Examples 1 to 5 are all prepared by the following method, and the specific steps are as follows:
[0043] (1) mixing the chemical components according to the ratio, and obtaining an automobile I-shaped front axle ingot through smelting and casting;
[0044] (2) Heat treatment process after casting: first, keep at 830℃±20℃ (Examples 1 to 5 are 810℃, 850℃, 830℃, 820℃ and 840℃, respectively) for 30 to 60min (Examples 1 to 5 are 30min, 60min, 45min, 40min and 50min, respectively), then water quench to room temperature, and then keep at 500 to 550℃ (Examples 1 to 5 are 500℃, 550℃, 520℃, 510℃ and 540℃, respectively) for 90 to 120min (Examples 1 to 5 are 90min, 120min, 100min, 110min and 95min, respectively), then water cool to room temperature.
[0045] Example 1
[0046] In this embodiment, the chemical composition of the high-performance and low-cost micro-alloy steel for the automobile I-shaped front axle is, by weight percentage, C: 0.41%, Mn: 0.55%, Si: 0.31%, Cr: 0.75%, Mo: 0.034%, Ti: 0.073%, S: 0.0055%, P: 0.0045%, O: 0.0025%, N: 0.0012%, and the balance is iron.
[0047] Example 2
[0048] In this embodiment, the chemical composition of the high-performance and low-cost micro-alloy steel for the automobile I-shaped front axle is, by weight percentage, C: 0.49%, Mn: 0.51%, Si: 0.50%, Cr: 0.85%, Mo: 0.04%, Ti: 0.08%, S: 0.0035%, P: 0.0065%, O: 0.0022%, N: 0.0011%, and the balance is iron.
[0049] Example 3
[0050] In this embodiment, the chemical composition of the high-performance and low-cost micro-alloy steel for the automobile I-shaped front axle is, by weight percentage, C: 0.36%, Mn: 0.60%, Si: 0.11%, Cr: 0.66%, Mo: 0.03%, Ti: 0.061%, S: 0.0045%, P: 0.0075%, O: 0.0036%, N: 0.0019%, and the balance is iron.
[0051] Example 4
[0052] In this embodiment, the chemical composition of the high-performance and low-cost micro-alloy steel for the automobile I-shaped front axle is, by weight percentage, C: 0.39%, Mn: 0.58%, Si: 0.22%, Cr: 0.71%, Mo: 0.033%, Ti: 0.066%, S: 0.0075%, P: 0.0085%, O: 0.0026%, N: 0.0014%, and the balance is iron.
[0053] Example 5
[0054] In this embodiment, the chemical composition of the high-performance and low-cost micro-alloy steel for the automobile I-shaped front axle is, by weight percentage, C: 0.45%, Mn: 0.53%, Si: 0.41%, Cr: 0.80%, Mo: 0.036%, Ti: 0.076%, S: 0.0033%, P: 0.0075%, O: 0.0021%, N: 0.0017%, and the balance is iron.
[0055] Comparative Example 1
[0056] In this comparative example, the Ti content in the high-performance, low-cost micro-alloy steel for the I-shaped front axle of an automobile is less than 0.01% by weight, and the other chemical compositions and heat treatment process are exactly the same as those in Example 1.
[0057] Comparative Example 2
[0058] In this comparative example, by weight percentage, the N content of the high-performance, low-cost micro-alloy steel for automobile I-shaped front axles is 0.01%, and the other chemical compositions and heat treatment processes are exactly the same as those in Example 2.
[0059] Comparative Example 3
[0060] In this comparative example, by weight percentage, the C and Ti contents of the high-performance and low-cost micro-alloy steel for automobile I-shaped front axles are 0.35% and 0.08%, respectively, and the other components and heat treatment process are exactly the same as those in Example 5.
[0061] As shown in Table 1, the atomic ratios of C and Ti and the mechanical properties in Examples 1 to 5 and Comparative Examples 1 to 3.
[0062] Table 1
[0063]
[0064] As can be seen from Table 1, the comprehensive performance of the inventive material is significantly improved by adding 0.06% to 0.08% optimized content of Ti on the basis of 40Cr material, the yield strength reaches more than 1063MPa, the tensile strength reaches more than 1165MPa, and especially the B50 fatigue performance is improved by more than 40% compared with the comparative example 1 without Ti. This is mainly attributed to the action mechanism of TiC precipitation phase refining grains. In the solid solution process at 810 to 850°C, TiC has extremely high thermodynamic stability and is distributed near the grain boundaries, which can effectively inhibit grain boundary migration and prevent grain growth, significantly improve the strength and toughness of the material, and obtain a martensitic matrix after water quenching; in the subsequent tempering process at 500 to 550°C, dispersed and uniformly distributed carbides are obtained on the martensitic matrix, and the best combination of material strength and plasticity is obtained.
[0065] like Figure 1 As shown, it can be seen from the metallographic structure of Example 1 of the present invention that the material matrix is a martensitic lath structure, which is different from the metallographic structure of Comparative Example 1. Figure 4 In contrast, the material has an optimized Ti content, and the grain refinement mechanism of the TiC precipitation phase during heat treatment causes the martensite laths and grains of the material to be significantly refined, and the organizational segregation during casting is also improved.
[0066] like Figure 2 As shown, it can be seen from the secondary electron microscopic structure of Example 1 of the present invention that the SEM structure of Example 1 is different from that of Comparative Example 1. Figure 5 In contrast, after adding a certain amount of Ti, the martensite laths are refined and the microstructure is uniform.
[0067] like Figure 3 As shown, in Example 2, two different sizes of TiC precipitates are formed at the grain boundary and inside the grain, and the size of the TiC precipitates at the original austenite grain boundary is about 480-520 nm, which plays the role of pinning the grain boundary and refining the martensite lath. The TiC in the martensite lath and inside the grain is dispersed and evenly distributed, and the size of the precipitates is between 20 and 50 nm.
[0068] like Figure 4-Figure 5 As shown in the figure, in Comparative Example 1, Ti is not added, and although the matrix maintains the martensitic lath morphology, the martensitic lath is relatively Figure 1 and Figure 2 The grains are obviously widened, the sizes of the precipitates are different, and they are not evenly distributed. Figure 4 The black part in the middle is tissue segregation. Figure 1 , due to the lack of addition of a certain amount of Ti, the organization segregation is serious.
[0069] like Figure 6As shown, the N content in Comparative Example 2 is as high as 0.01%, which is doubled compared with the requirement of the invention material N of N < 0.005%, resulting in the presence of TiN with obvious angular structure at the micron level in the matrix, which deteriorates the mechanical properties of the material, especially the fatigue performance, which is the lowest, reaching 81,000 times.
[0070] like Figure 7 As shown, from the tensile fracture of Comparative Example 2, it can be seen that the fracture crack source exists in TiN with large particles, the tensile fracture is a cleavage fracture, and the strength and plasticity of the material are the lowest.
[0071] The results of the embodiments show that the high-performance and low-cost micro-alloy steel for the front axle of the automobile I-shaped structure of the present invention is optimized by adding a certain content of Ti element, and the movement of the austenite grain boundary is suppressed by pinning the austenite grains with TiC, and fine grains are obtained, and the strength and hardness of the material are significantly improved. Combined with the matching quenching + tempering heat treatment system, tempered martensite structure and TiC carbide are obtained, and the strength is obtained while improving the toughness and plasticity of the invented material. In addition, by controlling the N element content, it is ensured that Ti can be completely dissolved into the matrix during the smelting process to avoid the liquid precipitation of the TiN precipitation phase. Finally, the yield strength reaches more than 1063MPa, the tensile strength reaches more than 1165MPa, the elongation reaches more than 10.5%, the cross-sectional shrinkage rate reaches more than 36%, and the B50 fatigue performance reaches more than 570,000 times. High-performance and low-cost micro-alloy steel for the front axle of the automobile I-shaped structure is obtained.
[0072] In particular, the embodiment of the present invention adopts the optimized main chemical composition of C: 0.35-0.50%, Ti: 0.06-0.08%, the C / Ti atomic ratio is controlled between 22.4 and 24.4, and a matching heat treatment process is adopted. The room temperature mechanical properties of the high-performance and low-cost micro-alloy steel for the automotive I-shaped front axle are as follows: yield strength 1063-1097MPa, tensile strength 1165-1192MPa, elongation 10.5-15.5%, cross-sectional shrinkage 36-55%, B50 fatigue life (life when the cumulative failure probability reaches 50%) 570,000-650,000 times.
[0073] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.
Claims
1. A high-performance and low-cost micro-alloy steel for automobile I-axles, characterized in that: Its chemical composition, in weight percentage, is: C: 0.35-0.50%, Mn: 0.50-0.60%, Si: 0.1-0.5%, Cr: 0.65-0.85%, Ti: 0.01-0.10%, Mo: 0.03-0.04%, P<0.01%, S<0.01%, O<0.0040%, N<0.0050%, and the balance is iron.
2. The high-performance and low-cost micro-alloyed steel for automobile I-axles according to claim 1 is characterized in that: Preferably, Ti: 0.060-0.08%, and the atomic ratio of C to Ti is controlled between 20-30.
3. The high-performance and low-cost micro-alloyed steel for automobile I-axles according to claim 1 is characterized in that: Preferably, N<0.0020%.
4. A method for preparing high-performance and low-cost micro-alloyed steel for automobile I-axles according to any one of claims 1 to 3, characterized in that: The steps include: (1) mixing the chemical components in proportion, and obtaining an automobile I-axle ingot through smelting and casting; (2) The obtained automobile I-axle ingot is directly heat treated.
5. The method for preparing high-performance and low-cost microalloyed steel for automobile I-axles according to claim 4, characterized in that: In step (2), the heat treatment process is: first, keep the temperature at 830°C ± 20°C for 30 to 60 minutes, and then quench with water to room temperature; then, keep the temperature at 500 to 550°C for 90 to 120 minutes, and then cool with water to room temperature.
6. The method for preparing high-performance and low-cost microalloyed steel for automobile I-axles according to claim 4, characterized in that: The performance indicators of high-performance and low-cost micro-alloyed steel for automobile I-beam axles after heat treatment are as follows: yield strength reaches more than 1000MPa, tensile strength reaches more than 1150MPa, elongation reaches more than 10%, cross-sectional shrinkage reaches more than 35%, and fatigue life B50 reaches more than 550,000 times.
Citation Information
Patent Citations
Steel for niobium-vanadium compound reinforced high-strength axle and production method thereof
CN108220778A
Cited By
Steel StE500N for engineering machinery axle and smelting process production control method thereof
CN120536669A
StE500N steel for engineering machinery axle and preparation method of StE500N steel
CN120796840A